Labour economics and public policy managing the labour markets for competitiveness - Chew, Soon Beng 1948- (World Scientific, 2017)
Market wages -- Efficiency wages -- Market constraint -- Wage subsidy -- Elasticity of labour demand -- Purchasing power of wages -- Macro-focused unions -- Unit labour cost -- Unit business cost